2013
DOI: 10.1007/s10764-013-9705-9
|View full text |Cite
|
Sign up to set email alerts
|

Color Vision Variation as Evidenced by Hybrid L/M Opsin Genes in Wild Populations of Trichromatic Alouatta New World Monkeys

Abstract: Platyrrhine (New World) monkeys possess highly polymorphic color vision owing to allelic variation of the single-locus L/M opsin gene on the X chromosome. Most species consist of female trichromats and female and male dichromats. Howlers (genus Alouatta) are an exception; they are considered to be routinely trichromatic with L and M opsin genes juxtaposed on the X chromosome, as seen in catarrhine primates (Old World monkeys, apes, and humans). Yet it is not known whether trichromacy is invariable in howlers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 61 publications
2
31
0
3
Order By: Relevance
“…Group size ranged from 7 (SE) to 13 (CG). Two females from CG group have previously been analyzed (Matsushita et al., ). It was not possible to match fecal samples to individual monkeys, as our sample collection did not coincide with behavioral observations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Group size ranged from 7 (SE) to 13 (CG). Two females from CG group have previously been analyzed (Matsushita et al., ). It was not possible to match fecal samples to individual monkeys, as our sample collection did not coincide with behavioral observations.…”
Section: Methodsmentioning
confidence: 99%
“…We targeted exon 3 and exon 5 for PCR and sequencing analyses. The PCR primers were set in the conserved region of the exons between the MWS and the LWS opsin genes of howler monkeys (GenBank accession numbers and : Matsushita et al., ): exon 3, GGGATCACAGGTCTCTGGTC and CCTGCTCCAACCAAAGATGGG, exon 5, GCAAAGCAGCAGAAAGAGTC and CTGCCGGTTCATAAAGACATAGAT. PCR was carried out at 94°C for 5 min followed by 40 cycles at 94°C 30 s, 62°C 30 s, and at 72°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…And recently, Matsushita et al ( 2013 ) reported that some individuals of A. palliata and A. pigra possess hybrid M-and L-opsin genes, resulting in anomalous trichromatic vision. Importantly, Alouatta also differs from other platyrrhine monkeys in having an unusually high density of cone photoreceptors in the fovea of the central retina (Franco et al 2000 ;Finlay et al 2008 ).…”
Section: The Sense Of Visionmentioning
confidence: 99%
“…The goals of these two volumes are to bring together expert scholars, many from habitat countries, to contribute to a comprehensive corpus that reviews, integrates, and evaluates current information on howler behavior, ecology, nutrition, morphology, physiology, reproduction, evolution, and conservation. Moreover, recently published studies on howler systematics, functional morphology, physiology, and nutritional ecology highlight the growing importance of the genus Alouatta as a comparative model for examining platyrrhine evolution and the parallel social and ecological problems faced by species of prosimians, New World monkeys, Old World monkeys, and apes (Rosenberger et al 2009 ;Garber and Kowalewski 2011 ;Benchimol and Peres 2014 ;Halenar and Rosenberger 2013 ;Matsushita et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%